Functional energetic responses and individual variance of the human brain revealed by quantitative imaging of adenosine triphosphate production rates. Issue 6 (June 2018) - Zhu, Xiao-Hong; Lee, Byeong-Yeul; Chen, Wei
Cellular ATP energy metabolism and regulation are essential for brain function and health. Given the high ATP expenditure at resting-state, it is not yet clear how the human brain at working-state can effectively regulate ATP production to meet higher energy requirement. Through quantitative measurement of regional cerebral ATP production rates and associated neurophysiological parameters in human visual cortex at rest and during visual stimulation, we found significant stimulus-induced and highly correlated neuroenergetic changes, indicating distinctive and complementary roles of the ATP synthesis reactions in supporting evoked neuronal activity and maintaining ATP homeostasis. We also uncovered large individual variances in the neuroenergetic responses and significant reductions in intracellular [H + ] and free [Mg 2+ ] during the stimulation. These results provide new insights into the mechanism underlying the brain ATP energy regulation and present a sensitive and much-needed neuroimaging tool for quantitatively assessing neuroenergetic state in healthy and diseased human brain.